Barriers to referral uptake from primary to secondary eye care in the L V Prasad Eye Institute Network in South India. - Debananda Padhy; Giridhar Pyda; Rohit C Khanna (PLoS ONE)
Purpose To investigate the barriers preventing referral uptake from primary care vision centres (VC) to higher level secondary centres (SC) in rural South India. Methodology This is a cross-sectional study conducted using data from 10 VCs surrounding an SC in Thoodukurthy village, Mahabubnagar district, Telangana, India. The study included 2,508 participants who received primary eye care at the VCs and referred to SC between July 1st to December 31st, 2019, and from July 1st to December 31st, 2020 respectively. Of these,1930 (76.9%) participants were available for the study. Participants were categorized as compliant if they visited the SC within one year of referral. Non-compliance was defined as failing to do so within that time. Interviews were conducted with non-compliant participants to understand their reasons for not seeking further care. Results Among the 1930 participants 1507 (78%) were interviewed; 938 (62.2%) were compliant, and 569 (37.8%) were non-compliant. The mean age was 54.64 years (SD:14.28 years) and 716 (47.5%) were female. Multivariable analysis showed participants not referred for teleophthalmology (OR:1.41,95%CI:1.00-1.99), unmarried participants (OR:1.32,95%CI:1.02-1.71) and participants without formal education (OR:1.44,95%CI:1.09-1.90) were more likely to be non-compliant. Participants living further from VCs (OR:0.98,95%CI: 0.98-0.99) had better compliance. The major barriers were attitudinal (60.5%), economic (12.1%) and other medical or Health-related barriers (9.3%). Conclusion The primary barriers to referral uptake were related to attitudes, economics, and medical. Participants not referred to teleophthalmology, unmarried, those without formal education, and those lived closer to VCs were more likely to be non-compliant. Addressing these barriers could improve the utilization of higher-level care services in this rural population.